A proposition is a collection of declarative statements that has either a truth value "true” or a truth value "false". A propositional consists of propositional variables and connectives. We denote the propositional variables by capital letters (A, B, etc). The connectives connect the propositional variables.
A predicate is an expression of one or more variables defined on some specific domain. A predicate with variables can be made a proposition by either assigning a value to the variable or by quantifying the variable.
The following are some examples of predicates −
Well Formed Formula (wff) is a predicate holding any of the following −
All propositional constants and propositional variables are wffs
If x is a variable and Y is a wff, ∀ x Y and ∃ x Y are also wff
Truth value and false values are wffs
Each atomic formula is a wff
All connectives connecting wffs are wffs
The variable of predicates is quantified by quantifiers. There are two types of quantifier in predicate logic − Universal Quantifier and Existential Quantifier.
Universal quantifier states that the statements within its scope are true for every value of the specific variable. It is denoted by the symbol ∀.
∀ x P(x) is read as for every value of x, P(x) is true.
Example − "Man is mortal" can be transformed into the propositional form ∀ x P(x) where P(x) is the predicate which denotes x is mortal and the universe of discourse is all men.
Existential quantifier states that the statements within its scope are true for some values of the specific variable. It is denoted by the symbol ∃.
∃ x P(x) is read as for some values of x, P(x) is true.
Example − "Some people are dishonest" can be transformed into the propositional form ∃ x P(x) where P(x) is the predicate which denotes x is dishonest and the universe of discourse is some people.
If we use a quantifier that appears within the scope of another quantifier, it is called nested quantifier.
∀ a ∃ b P (x, y) where P (a, b) denotes a + b = 0
∀ a ∀ b ∀ c P (a, b, c) where P (a, b) denotes + (b + c) = (a + b) + c
Note − ∀ a ∃ b P (x, y) ≠ ∃ a ∀ b P (x, y)